2017
DOI: 10.1039/c7ce01396e
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of scandium fluoride oriented single-crystalline rods and urchin-like structures by a gas–solution interface technique

Abstract: A facile and effective method to obtain urchin-like structures and ordered arrays of rod-like crystals of scandium fluoride by an interfacial interaction between solution and gaseous reagents (Gas-Solution Interface Technique, GSIT) is reported. The rod crystals with tetragonal crystal lattice can be as thin as ca. 200 nm and as long as ca. 7 μm. The effect of solution concentration and reaction time on the morphology of the product is reported. The synthesized crystals were characterized by SEM, TEM, HRTEM, X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In view of the above findings, it can be concluded that an important line of research is the study of phase formation mechanisms in the systems with nanoscale reagents, inter alia, with nanoscale spatial limitations, i.e. of the processes in nanoreactors [17,[192][193][194][195]. Not only the "soft chemistry" methods [5,13,37,41,59,97,196,197], but also the methods based on precursor combustion [11,61,95,99,190,[198][199][200], in particular, the solvent combustion method [11,16,21,22,62,95,99,190,[198][199][200] are effective for producing materials with a high proportion of nonautonomous phases.…”
Section: Fig 1 Dependence Of Nonautonomous Phase Volume Fraction Inmentioning
confidence: 99%
“…In view of the above findings, it can be concluded that an important line of research is the study of phase formation mechanisms in the systems with nanoscale reagents, inter alia, with nanoscale spatial limitations, i.e. of the processes in nanoreactors [17,[192][193][194][195]. Not only the "soft chemistry" methods [5,13,37,41,59,97,196,197], but also the methods based on precursor combustion [11,61,95,99,190,[198][199][200], in particular, the solvent combustion method [11,16,21,22,62,95,99,190,[198][199][200] are effective for producing materials with a high proportion of nonautonomous phases.…”
Section: Fig 1 Dependence Of Nonautonomous Phase Volume Fraction Inmentioning
confidence: 99%
“…In view of the above findings, it can be concluded that an important line of research is the study of phase formation mechanisms in the systems with nanoscale reagents, inter alia, with nanoscale spatial limitations, i.e. of the processes in nanoreactors [17,[192][193][194][195]. Not only the "soft chemistry" methods [5,13,37,41,59,97,196,197], but also the methods based on precursor combustion [11,61,95,99,190,[198][199][200], in particular, the solvent combustion method [11,16,21,22,62,95,99,190,[198][199][200] are effective for producing materials with a high proportion of nonautonomous phases.…”
Section: Fig 1 Dependence Of Nonautonomous Phase Volume Fraction Inmentioning
confidence: 99%
“…Using the Gas-Solution Interface Technique (GSIT), 2D crystals of Ag, 13 oxides, 14,15 and fluorides 16,17 of various transition metals were obtained. The ability of this method to accurately control the crystal morphology and packing density enables producing oriented crystal arrays, 18 hollow crystals, 19 and gradient films able to roll up into microscrolls when dried. 20 The GSIT synthesis of inorganic materials is carried out under "soft" chemistry conditions on a naturally flat liquid-gas interface, it requires no templates, organic additives, nor physical impacts such as microwave, ultrasonic or high temperature processing.…”
Section: Introductionmentioning
confidence: 99%